Anders Munk (1922-1999) - 70th anniversary of birth - Wanda Truszkowska (Acta Mycologica, 2014)
Biography of dr. Anders M u n k. Danish famous mycologist, born in Koldiog 1922 and died 1989 in Kopenhagęn, an excellent specialist in the matter Pyrenomycetes.